Dos direitos da personalidade e a lei de doação de órgãos: o que há para cartografar? - Dantas, Herlaine Roberta Nogueira (2010)
This study aimed at examining the representation and the level of knowledge as well as getting acquainted whether there had been significant divergence among three social groups of 3rd year Law students, 7th period Medical students at UFPB and a group of people from the Catholic Church in vila dos pescadores in João Pessoa - about organ donation, transplant law and ethical issues that raise questions. In order to accomplish the qualitative analysis, Bardin´s content analysis technique was applied in conjunction with the Chisquare test which was applied with significance level of 5% to quantitative data. The data revealed that most informants agree with organ donation, Although they are not acquainted with the law of transplants, and with the lack of confidence in the single list of recipients. The problem is that there is an encouragement to trades with organs and the possibility of any person legally authorized to donate organs in life. The statistically significant difference was observed in only two questions, ie, in response to the confidence in the diagnosis of brain death: 64% of 7th period Medical students at UFPB trust this diagnosis versus 12% of the evangelizing group of vila dos pescadores. The other difference refers to the answer about the confidence in the single list of recipients: 36% of the 7th period Medical students of UFPB said to trust the list versus 12% of the 3rd law students of UFPB. This is was a multidisciplinary study with Involvement of lawyers and doctors